Self rating of health is associated with stressful life events, social support and residency in East and West Berlin shortly after the fall of the wall. Issue 8 (1st August 2000) - Hillen, Thomas; Schaub, Rainer; Hiestermann, Angelika; Kirschner, Wolf; Robra, Bernt-Peter
Abstract : STUDY OBJECTIVE: To compare the health status and factors influencing the health of populations that had previously lived under different political systems. DESIGN: Cross sectional health and social survey using postal interviews. The relation between self reported health and psychosocial factors (stressful life events, social support, education, health promoting life style and health endangering behaviour) was investigated. To determine East-West differences a logistic regression model including interaction terms was fitted. SETTING: East and West Berlin shortly after reunification 1991. PARTICIPANTS: Representative sample of 4430 Berlin residents aged 18 years and over (response rate 63%). RESULTS: Of all respondents, 15.4% rated their health as unsatisfactory. Residents of East Berlin rated their health more frequently as unsatisfactory than residents of West Berlin (Orage adjusted = 1.29, 95%CI 1.08, 1.52), these differences occurred predominantly in the over 60 years age group. Logistic regression showed significant independent effects of stressful life events, social support, education, and health promoting life style on self rated health. The effects of education and health promoting life style were observed to be more pronounced in the western part of Berlin. Old age and female sex showed a stronger association with unsatisfactory health status in the eastern part of Berlin. CONCLUSIONS: For subjects aged over 60 years there was evidence that living in the former East Berlin had an adverse effect on health compared with West Berlin. The impact of education and a health promoting lifestyle on self rated health seemed to be weaker in a former socialist society compared with that of a Western democracy. This study supports an "additive model" rather than a "buffering model" in explaining the effects of psychosocial factors on health.